Studi Karakteristik Kuat Tekan Beton Geopolimer Berbahan Dasar Fly Ash - Ashad, Hanafi; Rezky Putra, Muhammad; Utina, Toni (Jurnal Teknik Sipil, 2023)
The use of concrete is generally used to make road pavement, building structures, foundations, roads, pedestrian bridges, parking structures, bases for fences/gates, and cement in brick or block walls, causing the demand for cement material to be increasingly high, building construction materials experts also conducted various research on concrete. One of the research carried out was on Geopolymer Concrete. Geopolymer concrete is a type of geosynthetic concrete that is made without using any portland cement as a binding agent, and as a substitute for portland cement, fly ash mixed with an alkali activator is used.Geopolymer concrete mix planning uses the weight comparison method for each concrete composition using a w/fa factor of 0.25. The test object is cylindrical in shape with an activator alkali ratio of Na2SiO3: NaOH (sodium silicate and sodium hydroxide) of 1/2, 2/2, 3/2, 4/2 and 5/2. Cylindrical specimens with a diameter of 10 cm and a height of 20 cm were tested for compressive strength at the age of 14 days and 28 days to see the development and comparison of each variation of the alkali activator mixture for the results of the concrete compressive strength values.The average compressive strength of Geopolymer concrete with an alkali activator composition ratio of 1/2 and 2/2 cannot be used as structural concrete because the concrete compressive strength test results are below 18 MPa and geopolymer concrete with an alkali activator composition ratio of 3/2 to 5/2 can be used as an alternative substitute for concrete. conventional because the results obtained have reached the minimum concrete compressive strength requirements for the structural concrete category, namely > 18 MPa. Keywords: Geopolymer Concrete, Alkali Activator, Fly Ash, Compressive Strength